VEGF inhibitors for anti-angiogenic therapy - Alitalo, Kari; Pytowski, Bronislaw (Henry Stewart Talks, 2007)
Antagonist monoclonal antibodies to VEGFR-3, Mode of action of antagonist monoclonal antibodies, Functional properties of antagonist antibodies to VEGFR-3, In vivo effects of anti-VEGFR-3 treatment on physiological lymphangiogenesis, Inhibition of pathological vessel growth in the cornea, Anti-angiogenic effect of antibodies to VEGFR-3 in tumors, Inhibition of lymphatic metastasis with antagonist antibodies to VEGFR-3, Role of VEGFR-3 in normal and pathological immune response
Archived at 2018/05/31